Influence of Self-Regulated Learning on Prospective Teachers’ Self-Efficacy, Study Habits, and Lifelong Learning Skills - Ms. Maryam Fatima; Ms. Iram Naz; Dr. Misbah Malik; Ms.Asma Akhtar, (Dialogue Social Science Review (DSSR), 2025)
This study examines the role of Self-Regulated Learning (SRL) in shaping self-efficacy and study habits of prospective teachers studying at the Institute of Education and Research, University of the Punjab. Self-Regulated Learning (SRL) is a key mediator of enhancing prospective teachers’ self-efficacy, study habits, and lifelong learning skills. It profoundly affects their personal traits and enable them to foster independent learning in their future classrooms. Grounded in Zimmerman’s cyclical model, it explores key SRL aspects like goal setting, self-regulation, reflection, and motivation for academic success. Using an interpretivist, qualitative approach, data were collected through semi-structured interviews with 10 prospective teachers (6 females, 4 males) studying at Institute of Education and Research University of the Punjab Lahore Pakistan. Thematic analysis revealed that SRL enhances intrinsic motivation, persistence, and proactive learning. Participants emphasized the importance of self-monitoring for progress, self-evaluation, performance and self-efficacy in overcoming challenges. They also reported that effective study time management and minimizing distractions further improved their academic performance. The respondents highlighted the potential of SRL to foster positive academic outcomes, advocating for its integration into learning environments for better academic results and future sustainability. Key words: Self-Regulated learning, Self-efficacy, Undergraduate students